Drzewa – pomniki przyrody jako element krajobrazu kulturowego - Agnieszka Affek-Starczewska; Krzysztof Starczewski; Zbigniew Pawlonka; Janina Skrzyczyńska (Studia Ecologiae et Bioethicae)
The history of the protection of the special qualities of trees is almost as old as humanity itself. !e protection of trees was mainly associated with a kind of sacrum, which surrounded old and large trees. There are plenty of reasons why old trees are protected, but their popularity as tourist attractions varies widely. !is study was an attempt at determining the attractiveness of monumental trees as monuments and a part of the cultural landscape. !e analysis was conducted on sites with monumental trees in six regions: Siedlce, Mińsk Mazowiecki, Biała Podlaska, Repki, Czeremcha, and Mrozy, as well as the towns: Siedlce, Biała Podlaska and Minsk Mazowiecki. Most of the monumental trees were found in alley systems and historical parks, formerly belonging to manors and palaces. Only a few were found in the &elds. In addition to the trees of native origin were introduced species, imported specially for cultivation in gardens and parks. Among these, the most numerous were specimens of small-leaved lime. English oak was somewhat less frequent.